Readiness of Flexible Working Arrangement: The Narrative Study of Flexibility Working Space at The Ministry of Finance, Indonesia - Salmon, Indra Pratama Putra (Yayasan Ilomata, 2024)
The background of this research is the flexible working arrangement system at the Ministry of Finance or the Ministry of Finance in the form of a flexible working space or FWS which has become a new working paradigm and has proven to be effective, has not been able to synthesize sustainable patterns and is still valid only as a privilege. This study aims to analyze the concept of FWS implementation in the Ministry of Finance and synthesize it in alternative sustainable FWS governance. The research uses qualitative methods and a narrative study approach. The research findings show that digital tools are a significant element in the FWS system and are proven to make FWS a system capable of optimizing performance productivity. Digital tools are also one of the driving factors for more flexible and accommodating work demands for employees at the Ministry of Finance. These two interrelated things then make FWS an alternative to new work procedures, which are projected to be not only employee privileges but also the majority of employees. As an implication of the research, an elaboration of the control and evaluation of the FWS, the system adaptability pattern and workload calibration on the FWS scheme is carried out, as well as the calculation of the benefit cost on an ongoing basis in the form of design determination and feasibility tests, periodic performance tests and optimization of the acceleration of the FWS system.